Highly sensitive selective sensing of nickel ions using repeatable fluorescence quenching-emerging of the CdTe quantum dots. (November 2017) - Zare, Hakimeh; Ghalkhani, Masoumeh; Akhavan, Omid; Taghavinia, Nima; Marandi, Maziar
Graphical abstract: A new and simple strategy was developed for the highly sensitive and selective detection of nickel ion using highly fluorescent water-soluble TGA-CdTe QDs as the fluorescence probes. Highlights: The high efficiency CdTe QDs was synthesized. The fluorescent sensor shows high selectivity and sensitivity to Ni 2+ ions. The sensor can be applied to environmental water samples with excellent sensitivity and selectivity. This sensor exhibits a low limit of detection of 7 nM for Ni 2+ . Abstract: Highly sensitive nickel sensor based on repeatable fluorescence quenching-emerging mechanism was developed. Highly luminescent thioglycolic acid capped CdTe nanocrystals in aqueous solution were applied as the fluorescence probe. These nanocrystals represented a considerable photoluminescence quantum yield as high as 61%. The florescence was quenched by addition of Ni ions to the CdTe nanocrystals solution. Then it was recovered by injection of the proper amount of dimethylglyoxime as the releasing reagent. The relative fluorescence intensity ( F 0 / F ) was linearly proportional to the concentration of nickel ions in the range of 0.01–10 μM, with detection limit as low as 7 nM. Described method is able to selectively determine Ni 2+ without any tangible influence of some potentially interfering ions such as Ag +, Cu 2+, Zn 2+, Co 2+ and Hg 2+ . The developed technique was employed for determination of Ni 2+ in different environmental water samples, and the results were verified by inductively coupled plasma-optical emission spectrometry.